Monitoring Kepatuhan Peraturan Kawasan Tanpa Rokok di Lingkungan Sekolah Kota Yogyakarta - Trisnowati, Heni; Marlinawati, Utari (Disease Prevention and Public Health Journal, 2020)
Background: Smoke-Free School (SFS) policy have been implemented since 2015. These regulations include elementary schools, junior high schools, senior high schools and vocational high schools both private and public. SFS policy aims to create a clean, healthy and smoke-free school environment. Beside, SFS policy is the only effective way to protect the community (school residents) from the dangers of smoke, but the regulation has not been fully implemented by schools in the city of Yogyakarta. This study aims to describe the compliance of SFSP in schools throughout the city of Yogyakarta and the challenges of implementing these regulations. Method: This study used a quantitative method with cross-sectional survey design and observation. The population in this study were all schools in the city of Yogyakarta including elementary, middle and high school or vocational schools. Total samples were 162 schools. The sampling technique used the Proportional Stratified Random Sampling method. Data was collected through one survey and analyzed descriptively using a computer system. Results: input indicators of SFS policy: 89.5% of schools in the Yogyakarta city already have a written policy; 88.3% of schools already have promotional media about smoking bans, 66% of schools already have personnel who monitor SFS policy; Process indicators of SFS policy: 88.9% had already received SFP socialization directly. Output indicator of SFP: there are 146 (90.1%) smoke-free schools in Yogyakarta. Barriers to the implementation of SFS policy include smoking behaviour of school residents, lack of ability to conduct assertiveness, environment and school policies have not to support Â SFS. Conclusion: The level of school compliance with SFS in the city of Yogyakarta is high. Socialization of SFS needs to be carried out continuously, especially for pickers (parents) and giving a strict sanction for those who violate SFS policy.